Magnetic reorientation and thermal stability in MnAs/GaAs (100) micro patterns driven by size effects - Tortarolo, Marina del Carmen (2012)
Size effects and their consequences in the thermal stability of the magnetization of the micro-sizedMnAs/GaAs(100) ribbons were studied by magnetic force microscopy. We found out that theorientation in which size is reduced plays a key role in the magnetic configuration and thermalstability of the micro-sized patterns. On the one hand, when reducing the size in the [0001]a-MnAs direction, the system shows an improvement in the thermal stability of the remanentmagnetization. On the other hand, when the size is reduced in the [11-20] a-MnAs direction, thesystem goes through a magnetic reconfiguration from in-plane magnetized to out-of-planemagnetized, which also improves the thermal stability.